Evolving Vision of Regulatory Science in the Global Medical Community. Issue 1 (13th September 2019) - Kondo, Tatsuya; Hayashi, Yoshikazu; Sato, Junko; Sekine, Shohko; Hoshino, Tatsuro; Sato, Daisaku
Abstract : "Regulatory science" (RS) has been defined in various ways, but, nevertheless, the definitions of RS in different parts of the world include many common elements. It seems to be a common view that RS is not basic or applied science but, rather, focuses on the estimation and prediction of safety and efficacy. Thus, we think RS overall should incorporate not only RS specifically for medical product assessment but also RS engineering to provide prediction and estimation tools for those purposes, including guideline/guidance development. It is important as well to consider the potential contribution of RS to rational medicine (i.e., to evidence‐based medicine in a broader context), and especially to real‐world evidence generation. We will look at how definitions of RS have evolved, and how we believe RS might develop in the future. Taking a patient‐centric view, we re‐emphasize RS is an ethical science contributing to society and human welfare.